2005
DOI: 10.1039/b501361e
|View full text |Cite
|
Sign up to set email alerts
|

PET fluoroionophores for Zn2+ and Cu2+: complexation and fluorescence behavior of anthracene derivatives having diethylamine, N-methylpiperazine and N,N-bis(2-picolyl)amine units

Abstract: Anthracene derivatives (1, 2) having one or two diethylamine (a), N-methyl-piperazine (b) and N,N-bis(2-dipicolyl)amine units (c) showed weak emission, suggesting that photoinduced electron transfer (PET) from the amine group to the excited anthracene occurs. The PET fluoroionophores (1, 2) were found to display unique photophysical properties in the presence of the guest metal salts. Complexation of diethylamine (1a, 2a) and N-methyl-piperazine derivatives (1b, 2b) with Ni 2+ , Cu 2+ and Zn 2+ enhanced the em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 27 publications
(19 reference statements)
1
25
0
Order By: Relevance
“…Here we present a new class of amino-functional rhodamines the pH-sensitivity of which originates from the intramolecular photoinduced electron transfer process (PET, [37–42] ) between non-protonated amino groups and the excited chromophore ( Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Here we present a new class of amino-functional rhodamines the pH-sensitivity of which originates from the intramolecular photoinduced electron transfer process (PET, [37–42] ) between non-protonated amino groups and the excited chromophore ( Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…De Silva et al 1,4,6 have created a photoinduced electron transfer PET fl uoroionophore consisting of an azacrown ether with an anthryl group. We have reported that multi-donor-spacer-multi-acceptor systems [7][8][9][10][11][12][13] such as diaza-18-crown-6 1 and diaza-12-crown-4 2 ethers, carrying two 9-anthrylmethyl groups, have a higher fluorescence switch-on ability for guest cation complexation than those of the corresponding monoazacrown derivatives Scheme 1 . Piperazine is widely used as a chelate.…”
Section: Introductionmentioning
confidence: 99%
“…A series of 2‐(stilben‐4‐yl)benzoxazole derivatives prepared by Andrzej et al was used as a dopant in the fabrication of organic light‐emitting diodes 15. Moreover, the anthracene group with rigid large π‐conjugated structure is generally used as matrix for synthesizing all sorts of optical compounds 16–19…”
Section: Introductionmentioning
confidence: 99%